The Comparison of the Monolingual and Bilingual Japanese Students in The English Achievement - Dewi, Ienneke Indra (Bina Nusantara University, 2007)
Article is intended to know whether the monolingual or bilingual Japanese students are better in the English achievement and whether the exposure of English influences the ability. The data were taken from 60 Japanese students who are supposed to fill in the questionnaires regarding their language background. The English achievement data were taken from the students’ scores in Senior High School National Examination and the data further were compared to the TOEFL English score. The analysis is carried out using ANOVA analysis. This research indicates that monolinguals are better learners in English and exposure is proved to influence the students’ ability in English.